Food insecurity as a risk factor of sarcopenic obesity in older adults - Fonseca-Pérez, Diana; Arteaga-Pazmiño, Cecilia; Maza-Moscoso, Claudia P.; Flores-Madrid, Sara; Álvarez-Córdova, Ludwig (Frontiers in Nutrition, 2022)
Sarcopenic obesity is characterized by the loss of muscle strength, mass and muscle functionality and increased adipose tissue (obesity) according to different criteria and cut-off points. The prevalence of sarcopenic obesity among older adults is growing worldwide, and many factors are involved in its development. Diet and food security have been described as the main contributors to the development of obesity and sarcopenia. Food insecurity consists of limited or uncertain access to adequate and nutritious foods. This narrative review aims to summarize the existing data on food insecurity as a risk factor for sarcopenic obesity in the elderly